Pistoning versus Holding Dry Needling for Pain, Disability, and Cervical ROM in Upper Trapezius Myofascial Pain Syndrome: Pistoning versus Cervical ROM in Upper Trapezius MPS - Ebrahimi, Zohreh; Khan, Muhammad Atif; Islam, Hira; Begum, Nigar; Shirazi, Hasan; Mubeen, Muhammad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Myofascial Pain Syndrome is a prevalent musculoskeletal pain that is characterized by myofascial trigger points. Myofascial trigger points often occur in the upper trapezius. Objectives: To determine the comparison of the effects of the use of pistoning on the pain intensity, the presence of disability, and cervical range of motion in adults with upper trapezius myofascial pain syndrome compared to holding dry needling. Methods: It was a quasi-experimental study in which twenty-four participants were randomized into the pistoning dry needling group (twelve subjects) or the holding dry needling group (twelve subjects). The use of interventions was in three sessions weekly over a three-week continuous period. The outcome measures (prone to pain measured with the help of the Visual Analogue Scale, cervical range of motion assessed with the help of the goniometer, disability measured with the Disabilities of the Arm, Shoulder and Hand questionnaire) were compared at the baseline and one week after the last intervention. Results: The intensity of pain and disability related to the pain was reduced, and the range of motion of the cervix was higher in all directions: flexion, extension, lateral flexion, and rotation. Nonetheless, between-group analysis showed that there were no statistically significant differences in the extent of improvement in any of the outcome measures, which showed that the two techniques were equally effective. Conclusions: Pistoning and holding the dry needling method are effective in pain reduction, cervical range of motion, and disability among upper trapezius myofascial pain syndrome patients.